Find the value of c o s 2 4 ∘ + c o s 4 8 ∘ + c o s 9 6 ∘ + c o s 1 6 8 ∘
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
cos 2 4 ∘ + cos 4 8 ∘ + cos 9 6 ∘ + cos 1 6 8 ∘ = cos 2 4 ∘ + cos 9 6 ∘ + cos 4 8 ∘ − cos 1 2 ∘ = ( 2 cos 6 0 ∘ cos 3 6 ∘ ) + ( − 2 sin 3 0 ∘ sin 1 8 ∘ ) = cos 3 6 ∘ − sin 1 8 ∘ = sin 5 4 ∘ − sin 1 8 ∘ = cos 1 8 ∘ 2 cos 3 6 ∘ sin 1 8 ∘ cos 1 8 ∘ = 2 cos 1 8 ∘ 2 cos 3 6 ∘ sin 3 6 ∘ = 2 cos 1 8 ∘ sin 7 2 ∘ = 2 1
use complex numbers..becomes a simple GP
Problem Loading...
Note Loading...
Set Loading...
An inefficient solution—due to the fact that I have incomprehensive knowledge of this subject—based off of sum-to-product formulas and the exact value of cos 36º
Given: cos 2 4 º + cos 4 8 º + cos 9 6 º + cos 1 6 8 º ⇒ ( cos 2 4 º + cos 1 6 8 º ) + ( cos 4 8 º + cos 9 6 º ) ⇒ 2 cos ( 2 2 4 º + 1 6 8 º ) cos ( 2 2 4 º − 1 6 8 º ) + 2 cos ( 2 4 8 º + 9 6 º ) cos ( 2 4 8 º − 9 6 º ) ⇒ 2 cos 9 6 º cos 7 2 º + 2 cos 7 2 º cos 2 4 º ⇒ 2 cos 7 2 º ( cos 9 6 º + cos 2 4 º ) ⇒ 2 cos 7 2 º ( 2 cos ( 2 9 6 º + 2 4 º ) cos ( 2 9 6 º − 2 4 º ) ) ⇒ 2 cos 7 2 º cos 3 6 º
Applying double-angle formula: cos 2 θ = 2 cos 2 θ − 1 ⇒ cos 7 2 º = 2 cos 2 3 6 º − 1 = 2 ( 4 5 + 1 ) 2 − 1 ⇒ cos 7 2 º = 4 5 − 1
Plugging in we get: 2 cos 7 2 º cos 3 6 º = 2 ( 4 5 + 1 ) ( 4 5 − 1 ) = 2 ( 1 6 5 − 1 ) = 2 1 = 0 . 5